The Effectiveness of Telemedicine for Glycemic (Hba1c) Management of Patients with Diabetes Mellitus Type 2: A Meta-Analysis - Putri, Santy Irene; Supriyono, Nisa'i Daramita; Fajriah, Asruria Sani; Akbar, Prima Soultoni (Majalah Kesehatan Indonesia, 2025)
Diabetes mellitus (DM) is a degenerative disease caused by genetic and environmental factors. Therefore, patients with DM type 2 requires regular control. One of the health facilities that allows a fine control and follow up over patients with DM is telemedicine. This study aimed to estimate the average effectiveness of telemedicine on glycemic management (HbA1C) of patients with DM type 2. The current research employed a systematic review with meta-analysis research design. The subjects of the study were articles published in 2005 - 2021. The article search was conducted for a maximum of 1 month over journal databases: PubMed, ScienceDirect, and Google Scholar. The primary study employed Randomized Controlled Trial with articles search according to the established PICO model, where P (Population), in this sense, patients suffering from DM type 2, I (Intervention) which was Telemedicine, C (Comparison) or non-telemedicine, and O (Outcome), which was glycemic management (HbA1c). A total of 10 primary studies were assessed with Critical Appraisal Center for Evidence-Based Medicine (CEBM). The results demonstrated that telemedicine is effective in glycemic management (HbA1c) of DM type-2 patients with a p-value of <0.05, namely p<0.04 and a standardized mean difference (SMD) value of -0.24 (95% CI, -0.34 to -0.15). The results of this meta-analysis provide strong scientific evidence regarding the benefits of telemedicine in lowering HbA1c levels in patients with type 2 DM.